1995
DOI: 10.1093/clinchem/41.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the number of apolipoprotein(a) kringle 4 domains on immunochemical measurements of lipoprotein(a)

Abstract: Lipoprotein(a) [Lp(a)] has been measured in numerous clinical and epidemiological studies by a variety of immunochemical methods. However, little, if any, consideration has been given to the confounding effect of the size heterogeneity of apolipoprotein(a) [apo(a)] on the measurement of Lp(a). We developed three direct-binding enzyme-linked immunosorbent assays (ELISAs) with detecting antibodies of different specificities to evaluate the effect of apo(a) size on Lp(a) measurement. The three assays used the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(114 citation statements)
references
References 21 publications
0
101
0
Order By: Relevance
“…Apo(a) concentration can be accurately determined by a double monoclonal antibody-based enzyme-linked immunoassay that is by design, insensitive to Apo(a) size heterogeneity, NWLRL ELISA. [12] Alternatively, a limited number of commercially available assays exist including an immunoturbidimetric assay that uses an antibody that does not cross-react with plasminogen or apolipoproteinB as well as a lectin-based assay that captures Lp(a) and measures the cholesterol content in the particle. [13] Lamon-Fava et al compared the commercially available assays to the Northwest Lipid Research Laboratories (NWLRL) ELISA and found that they were well correlated.…”
mentioning
confidence: 99%
“…Apo(a) concentration can be accurately determined by a double monoclonal antibody-based enzyme-linked immunoassay that is by design, insensitive to Apo(a) size heterogeneity, NWLRL ELISA. [12] Alternatively, a limited number of commercially available assays exist including an immunoturbidimetric assay that uses an antibody that does not cross-react with plasminogen or apolipoproteinB as well as a lectin-based assay that captures Lp(a) and measures the cholesterol content in the particle. [13] Lamon-Fava et al compared the commercially available assays to the Northwest Lipid Research Laboratories (NWLRL) ELISA and found that they were well correlated.…”
mentioning
confidence: 99%
“…Plasma samples from healthy individuals matched for race, sex and size of apo(a) isoforms were collected in an identical fashion (see Table 1). Plasma Lp(a) level was determined by ELISA using IgG-a6 as capture antibody, which is a mouse monoclonal antibody (Mab) directed against the common K4-type 2 repeat, and IgG-a40 as the detecting Mab, whose epitope is located in the KCtype 9 repeat (Marcovina et al 1995). Plasma Lp(a) levels were also quantitated in a separate assay using the same capture antibody but IgG-a5, which is an antiapo(a) K4-type 1 and 2 Mab, as the detecting antibody.…”
Section: Methodsmentioning
confidence: 99%
“…These assays would be expected to over-estimate the plasma levels of Lp(a) in individuals with high molecular weight apo (a) isoforms, since they have more copies of the epitope of the antibody. Recently Marcovina and her colleagues have developed an apo(a) ELISA assay that uses monoclonal antibodies directed against a unique epitope in the apo(a) molecule, which resides outside the common K4-type 2 region (Marcovina et al 1995). She has shown that this assay is independent of the size of the apo(a) isoform.…”
mentioning
confidence: 99%
“…The LDL fraction was harvested and washed by centrifugation at d c 1.063 g/ml for a further 2 h. The protein concentration of the isolated LDL was determined by the method of Bradford using bovine serum albumin (BSA) as a standard. Lp(a) was isolated from human plasma as previously described (Marcovina et al 1995).…”
Section: Lipoprotein Purificationmentioning
confidence: 99%